Incorporating Continuity in a 7-On 7-Off Hospitalist Model and the Correlation With Patient Handoffs and Length of Stay. (November 2019) - O'Donnell, Christopher M.; Stern, Marsha; Leong, Traci; Molitch-Hou, Ethan; Mitchell, Bruce
Little research in hospital medicine examines the effects of hospitalist continuity on patient outcomes. This study implemented a novel staffing model with approximately half of rounding teams starting their 7-day workweek on Monday and the others on Friday. Teams admitted their own patients on their first 4 days with additional nighttime admissions handed off to those teams. No admissions were given to teams on their last 3 days. Length of stay was significantly reduced from 6.34 days in 2015 to 5.7 days in 2016 ( P < .002) with a significant decrease in handoffs. There was an increase in odds ratio of death (1.37, SE = .128) with each additional hospitalist involved in a patient's care while adjusting for year and number of patient diagnoses ( P < .001). There was no statistical difference in charges, 30-day readmissions, or mortality between years.